PENGUATAN KETERAMPILAN SOSIAL PESERTA DIDIK DALAM PEMBELAJARAN IPS - Wibowati Oktina, Angkat (Penerbit CV Tentrem Karya Nusa, 2018)
In the globalization era, many influences have penetrated various joints of life. These influences cause social problems such as individualism, selfishness, lack of effective communication, low empathy, lack of sense of responsibility, low discipline level, lack of cooperation and interaction in community life. Social sciences education has a very important role in developing social skills of students, by mastering social skills, students are expected to live more functionally and meaningfully in the era of globalization.Key Words: Social Skills, Social Sciences